PENINGKATAN HASIL BELAJAR IPA SISWA KELAS IV SD MELALUI PETA KONSEP - pariang sonang siregar (Jurnal Inovasi Sekolah Dasar, 2016)
Abstract: This study was conducted in Class IV Elementary School 002 Rambah. Learning science in the fourth grade was not yet satisfactory, so it was held applied research in science learning through the use of concept maps. This study was aim at improving learning outcomes and the activities of the fourth grade students of SD Negeri 002 Rambah in learning science through concept maps. This research was a classroom action research conducted in two cycles. The procedure of this research was with each cycle consisting of planning, implementation, observation, and reflection. Data were collected through tests and observation. The results showed an increase learning outcomes and student activity. From the observation showed that an increase in the average class in the first cycle is 69.44 into 85.25 in the second cycle. Student learning outcomes increased from 35% to 90%. Students used to develop the concept and could give other examples based on the chart and concepts are provided. Keywords: Learning, Learning Outcomes, Concept Maps  Abstrak: Penelitian ini dilaksanakan pada Siswa Kelas IV SD Negeri 002 Rambah. Pembelajaran IPA di kelas IV masih tergolong belum memuaskan, sehingga diadakan penelitian terapan dalam pembelajaran IPA melalui penggunaan peta konsep. Penelitian ini bertujuan untuk meningkatkan hasil belajar dan aktivitas siswa kelas IV SD Negeri 002 Rambah pada pembelajaran IPA melalui peta konsep. Penelitian ini merupakan Penelitian Tindakan Kelas yang diadakan dengan dua siklus. Prosedur penelitian ini adalah dengan setiap siklus terdiri perencanaan, pelaksanaan, pengamatan, dan refleksi. Data dikumpulkan melalui tes dan observasi. Hasil penelitian menunjukkan adanya peningkatan hasil belajar dan aktivitas siswa. Dari hasil observasi memperlihatkan bahwa terjadi peningkatan rata-rata kelas yang pada siklus I yaitu 69,44 menjadi 85,25 pada siklus II. Hasil belajar siswa dari 35% meningkat menjadi 90%. Siswa terbiasa mengembangkan konsep dan bisa memberikan contoh lain berdasarkan bagan dan konsep yang disediakan. Kata Kunci: Pembelajaran, Hasil Belajar, Peta Konsep